2022
DOI: 10.1097/bpo.0000000000002071
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Clavicle Fractures: Does Clavicle Fracture Morphology Affect Brachial Plexus Injury?

Abstract: Background: Newborn clavicle fractures and brachial plexus injuries (BPIs) are rare but serious perinatal complications. Methods: The aim of this study was to examine the clinical relationship between the fracture morphology (spiral, oblique, transfer) of clavicle fractures that develop during delivery in newborns and BPI. We retrospectively reviewed all perinatal clavicle fractures diagnosed at our institution over 6 years. Results: The study included 55 newborn infants with perinatal clavicle fracture. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…Entre los factores de riesgo más frecuentes de la fractura clavicular se encuentra la macrosomía, distocia de hombros, multiparidad y partos vaginales instrumentales. Cuando la fractura se secundaria a distocia de hombro frecuentemente se acompaña de lesión del (17)(18)(19)(20) plexo braquial .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Entre los factores de riesgo más frecuentes de la fractura clavicular se encuentra la macrosomía, distocia de hombros, multiparidad y partos vaginales instrumentales. Cuando la fractura se secundaria a distocia de hombro frecuentemente se acompaña de lesión del (17)(18)(19)(20) plexo braquial .…”
Section: Discussionunclassified
“…Existe un estudio que revela que las lesiones del plexo braquial que ocurrieron en ausencia de distocia de hombros tenían una tasa más (6) alta de fractura de clavícula concomitante . El tipo de fractura de la clavícula, como las oblicuas o en espiral, posiblemente predisponga a mayor frecuencia de (19) lesión del plexo braquial .…”
Section: Discussionunclassified
“…The study also found a statistically significant correlation between spiral and oblique clavicle fracture morphology and development of brachial plexus injury. 25 …”
Section: Anatomy Epidemiology and Classificationmentioning
confidence: 99%